Evaluasi peruntukan TPU di Kecamatan Sijunjung Pada Rencana Detail Tata Ruang Kawasan Perkotaan Muaro Sijunjung - Ulyadi Adam; yurni suasti (JURUSAN GEOGRAFI FIS UNP, 2020)
ABSTRACT The purpose of this research is to evaluate about Land Suitability and land allotment availability prediction of Public Burial Space in District Sijunjung of Sijunjung Regency on the Detail Spatial Plan of the Muaro Sijunjung Urban Area 2017-2037. The method used is descriptive with a quantitative approach. The data used in this research are primary and secondary data. The object of this research is the Public Burial Space in District Sijunjung of Sijunjung Regency on the Detail Spatial Plan of the Muaro Sijunjung Urban Area. Data analysis techniques by overlay way and matching the suitability criteria and the death average number calculation to find out the availability of public burial space land to the end of the validity period of Detailed Spatial Plan. The result of this research are : 1) Knowing the land suitability for the each Public Burial Space which allotment in the DSP Muaro Sijunjung Urban Area. 2) Knowing the land availability of the Public Burial Space